(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
This paper analyzes the musicalization of the fiction present in Vals, the most valued novel of Francesc Trabal. The present article suggests a different reading of this novel based on the concept of intermediality and through two axes: imitation and thematization (paratextual, contextual and intratextual one). In this sense, a very close relation between this musicalized fiction and the notion of metafictional irony is observed and it helps to understand the ludic proposal established by Trabal.